2001
DOI: 10.1051/0004-6361:20010616
|View full text |Cite
|
Sign up to set email alerts
|

ASCA observations of massive medium-distant clusters of galaxies. II.

Abstract: Abstract.We have selected seven medium-distant clusters of galaxies (z ∼ 0.1-0.3) for multi-wavelength observations with the goal of investigating their dynamical state. Following Paper I (Pierre et al. 1999) which reported the ASCA results about two of them, we present here the analysis of the ASCA observations of the other five clusters; RX J1023.8-2715 (A 3444), RX J1031.6-2607, RX J1050.5-0236 (A 1111), RX J1203.2-2131 (A 1451), and RX J1314.5-2517. Except for RX J1031.6, whose X-ray emission turned out to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
(23 reference statements)
1
8
0
Order By: Relevance
“…This is achieved by considering the highest redshift cluster in the control group: Abell 2255. For this cluster, the SDSS limiting 1 We re-affirm the note made by Valtchanov et al (2002) about Abell 1451 (T X = 13.4 keV; Matsumoto et al 2001) possessing a very significant deviation away from the L X -T X scaling relation (e.g., Popesso et al 2005). This cluster merits future follow-up to discern the impact and potential cause of such an extreme temperature.…”
Section: Cluster Sub-structuresupporting
confidence: 64%
“…This is achieved by considering the highest redshift cluster in the control group: Abell 2255. For this cluster, the SDSS limiting 1 We re-affirm the note made by Valtchanov et al (2002) about Abell 1451 (T X = 13.4 keV; Matsumoto et al 2001) possessing a very significant deviation away from the L X -T X scaling relation (e.g., Popesso et al 2005). This cluster merits future follow-up to discern the impact and potential cause of such an extreme temperature.…”
Section: Cluster Sub-structuresupporting
confidence: 64%
“…There is an X-ray emitting star in the south of the cluster whose X-ray emission was deblended. Nine coincident galaxy redshifts leave no doubt about the existence of a cluster at this position (see also the ASCA study of Matsumoto et al 2001). …”
Section: Rxcj00143-6604 A2746 (Also Included In Xbacs)mentioning
confidence: 97%
“…Properties of the two clusters. References: Abell (1958), Abell et al (1989) for the coordinates and richness; Bautz & Morgan (1970) for classification for Abell 1451; coordinates for RXJ1314−25 are from RASS (Voges et al 1999); T X and L X in the 2-10 keV band are from Matsumoto et al (2001); redshift and σ v are from this paper; the apparent magnitude of an L * galaxy was calculated using M * (B j ) = −21.8, obtained by adjusting the Lumsden et al (1997) was equipped with EFOSC1 (ESO Faint Object Spectrograph and Camera), Tektronix 512 × 512 CCD (pixel size 27 µm and 0.61 /pixel) and Grism B300, covering the range 3740-6950 Å, with central wavelength 5250 Å and dispersion of 6.2 Å/pixel. The observations in 1999 were performed with EFOSC2, CCD #40 2048 × 2048 (pixel size 15 µm, 0.157 /pixel) and Grism O300 which covers 3860-8070 Å with central wavelength 5000 Å and dispersion 2.06 Å/pixel.…”
Section: Observations and Reductionmentioning
confidence: 99%
“…By means of EXSAS (Zimmermann et al 1994), the observed count-rate is then used to normalize the spectral modela Raymond & Smith (1977) thermal plasma emission, convolved by the ROSAT/HRI response function, with temperature and metallicity from ASCA data (Matsumoto et al 2001) and line-of-sight Galactic absorption by H I from Dickey & Lockman (1990). The spectrum is then integrated to derive the flux and cluster rest frame luminosity in the "standard" X-ray bands [0.5-2] and [2-10] keV.…”
Section: X-ray Propertiesmentioning
confidence: 99%
See 1 more Smart Citation